1984
DOI: 10.1016/0014-5793(84)80060-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of β‐oxidation and proton conductance pathway of brown adipose tissue in hypo‐ and hyperinsulinemic states

Abstract: The metabolic capacity of interscapular brown adipose tissue of hypoinsulinemic (diabetic) rats is decreased and a reduced &oxidative capacity contributes to this metabolic alteration. It was thus of interest to compare, in diabetic and in chronically (8 days) insulin-infused rats, the &oxidative capacity and indices of the thermogenic state (GDP-binding and 32000 A4, protein) in this tissue. Mitochondrial GDP-binding and 32000 IV, protein were both decreased in diabetic rats compared to appropriate controls a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Such differences in sensitivity are consistent with reduced plasma insulin levels in vivo [12, 311 and insulin sensitivity increased [31] in cold exposure, and indicate greater insulin sensitivity of BAT of the cold-acclimated animal compared with that of the animal at thermoneutrality. Chronic insulin administration has been reported to increase BAT P-oxidative capacity by raising mitochondrial protonophore concentration in vivo [32], but the acute effects of insulin in vitro are less well defined. At supraphysiological concentrations, inhibition of Po?…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in sensitivity are consistent with reduced plasma insulin levels in vivo [12, 311 and insulin sensitivity increased [31] in cold exposure, and indicate greater insulin sensitivity of BAT of the cold-acclimated animal compared with that of the animal at thermoneutrality. Chronic insulin administration has been reported to increase BAT P-oxidative capacity by raising mitochondrial protonophore concentration in vivo [32], but the acute effects of insulin in vitro are less well defined. At supraphysiological concentrations, inhibition of Po?…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown before that in diabetic rats or mice, COX activity and mitochondrial protein content were decreased and could be at least partially restored by insulin treatment (13,14). UCP content and proton conductance of rat brown fat are also reduced in a hypoinsulinemic state (39). Geloen and Trahurn (14) could also demonstrate a stimulating effect of insulin on UCP levels, which they showed to be partly, but not entirely mediated by the sympathetic nervous system.…”
Section: Brown Adipocyte Thermogenesis Is Regulated By Several Hormonmentioning
confidence: 94%
“…We found that insulin increased the BAT mass, the metabolic capacity of the tissue, and the concentration of uncoupling protein in BAT mitochondria (Seydoux et al, 1984). Nevertheless, these effects of insulin on BAT were probably both direct (effects on the tissue) and indirect (via activation of the ventromedial hypothalamic nucleus which, in turn, activates the sympathetic fibres innervating BAT) (see discussion by Ricquier and (Jansky, 1973), we examined the role of BAT sympathetic innervation in the trophic response of this tissue during the prolonged exposure of rats to cold.…”
Section: Introductionmentioning
confidence: 67%